Activism in translation: Yan Fu’s translational activism against foreign imperialism in late Qing China - Wang, Xiaorui (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
The concept of translational activism underscores the ways translation has been used to promote social change. Translation and activism as an emerging area of interest in Translation Studies have attracted growing scholarly attention. Nevertheless, few studies have been conducted on activist translation in the context of China. This study examines translational activism against foreign imperialism through a case study on Yan Fu, a pioneer activist translator in late Qing China. Tymoczko’s concepts of resistance and engagement are used as descriptive categories for the empirical analysis. The appraisal framework is adopted as the analytical tool to address Yan Fu’s positioning and activist intervention. It is found that Yan pursued two complementary forms of activism in his translation: Yan demonstrates his resistance to foreign imperialism by criticising foreign aggression and resisting imperial privileges; while Yan manifests his engagement by disclosing the national crisis, inspiring patriotism and calling for action. As textual intervention has received little attention in activist translation, the present study fills this gap by examining the linguistic and textual manifestations of Yan’s activist intervention. In addition to applying the new theoretical lens of activism to examine Yan’s translation practice, the present study makes a theoretical contribution by adopting the appraisal framework in the area of translation and activism.